Using subject headings for online retrieval theory, practice, and potential - Vizine-Goetz, Diane (Academic Press, 1994)
Using Subject Headings for Online Retrieval is an indispensable tool for online system designers who are grappling with developing new systems or refining existing ones. This ready reference describes subject analysis and subject searching in online catalogs, including the limitations of retrieval, and demonstrates how such limitations can be overcome through system design and programming. The practical reference also describes the Library of Congress Subject Headings (LCSH) system and system characteristics; it shows how information is stored in machine-readable files; and it offers examples of and recommendations for successful retrieval methods. Tables are included to support these recommendations, and diagrams, graphs, and bar charts are used to provide results of data analysis. Practitioners in institutions using or considering the installation of an online catalog will continuously consult this book to generate specifications. The book also appeals to researchers in library systems, information retrieval, and user behavior because it details the results of an extensive, empirical study of the subject terms entered into online systems by end users. It also addresses the needs of advanced students in library schools and instructors in library automation, information retrieval, cataloging, indexing, and user behavior. It overviews the LCSH system and system characteristics. It describes how information is stored in machine-readable files. It offers examples of and recommendations for successful retrieval methods. Empirical evidence supports recommendations.
"Published under the auspices of OCLC Online Computer Library Center, Inc."
Keywords: Online bibliographic searching.; Subject headings.; Online library catalogs -- Subject access.; elektronické knihy; electronic books